On the complementarity of satellite surface velocity and altimetry observation networks in the Mercator ocean analysis and forecasting system: first insights - Isabelle Mirouze; Elisabeth Rémy; Giovanni Ruggiero; Mathieu Hamon; Jean-Michel Lellouche; Gérald Dibarboure; Yannice Faugère (Frontiers in Marine Science, 2026)
In recent years, the accuracy of ocean forecasts has significantly improved thanks to spatial altimetry. However, despite their importance, forecasting accurate currents is still a challenge. Therefore, satellite missions are proposed to provide measurements of surface velocity on a global coverage. The Ocean DYnamics and Surface Exchange with the Atmosphere (ODYSEA) mission of the National Aeronautics and Space Administration (NASA) and Centre National d’Etudes Spatiales (CNES) is currently competing for selection in the Earth System Explorers program. As part of the preliminary studies for ODYSEA, we have carried out Observing System Simulation Experiments (OSSEs) to assess the impact of assimilating these prospective observations in terms of Root Mean Square differences of the model state variables to a reference run. We focus on disentangling the impact of the ODYSEA observations from the impact of the observations provided by altimetry, on large scale, and checking the complementarity of these networks to avoid redundant information. We show that zonal velocity out of the Equator, sea surface height and surface salinity are mainly constrained by altimetry. Conversely, the meridional velocity is mainly constrained by velocity observations. Moreover, these latter observations help better prescribing both components of velocity at the Equator as well as the sea surface temperature in the Eastern Pacific. They also tend to significantly improve surface salinity in some regions where freshwater input occurs. Altimetry and surface velocity observations are complementary, and when they are assimilated together, all the model state variables are improved in all regions compared to assimilating altimetry only.